2016
DOI: 10.1111/1471-0528.13824
|View full text |Cite
|
Sign up to set email alerts
|

Educational effectiveness of gynaecological teaching associates: a multi‐centre randomised controlled trial

Abstract: Objective To evaluate, among medical students learning the female pelvic examination, the added benefits of training by gynaecological teaching associates compared with training involving a manikin only.Design Randomised controlled trial.Setting Nine university teaching hospitals.Population Ninety-four medical students recruited prior to commencing a 4-week obstetrics and gynaecology rotation.Methods The control training consisted of lectures, demonstration of the pelvic examination on a manikin, and opportuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 10 publications
0
13
0
1
Order By: Relevance
“…Results of the studies in this category suggest that utilising patients as teachers and assessors works best when it is possible to construct standardised assessment checklists and scoring criteria. This finding was more or less consistent across all of the Level 4 studies, with a further finding that, when tested, the improvements weren't sustained at Objective Structured Clinical Examination (OSCE) or follow up (Duffy 2016, Gruppen 1996, Livingstone 1980, Smith 2000.…”
mentioning
confidence: 76%
See 3 more Smart Citations
“…Results of the studies in this category suggest that utilising patients as teachers and assessors works best when it is possible to construct standardised assessment checklists and scoring criteria. This finding was more or less consistent across all of the Level 4 studies, with a further finding that, when tested, the improvements weren't sustained at Objective Structured Clinical Examination (OSCE) or follow up (Duffy 2016, Gruppen 1996, Livingstone 1980, Smith 2000.…”
mentioning
confidence: 76%
“…Of these, two (Duffy 2016 andHendry 1999) concluded that patient led teaching had a moderate effect on learning outcomes, Jha (2015) concluded that patient-led teaching was no more effective than faculty-led teaching and Humphrey-Murto (2014) found that faculty-led teaching was more effective in MSK examination than patient-led teaching.…”
Section: Study Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Thirdly, obtaining clinical experience is increasingly difficult as patients are reluctant to undergo intimate examinations for teaching purposes. Training with gynecological teaching associates is a viable alternative, but can be expensive. As a consequence, education is shifting toward simulation‐based training.…”
Section: Introductionmentioning
confidence: 99%